Marine fisheries in Kerala, India: An extension perspective - vk, sajesh; A, Suresh; Mohanty, A.K. (Fishery Technology, 2023)
The marine fisheries sector of Kerala has an important role in the economy of the state in terms of food, nutrition, employment and export earnings. But, the sector is facing multitude of challenges that negatively impact the livelihood of fisherfolk. Consolidating the gains and mitigating the challenges requires a reinvented extension system in the marine fisheries sector, which goes beyond the traditional technology transfer paradigm to a broadbased extension-plus approach. The focus needs to be shifted from enhancing production to enhancing income of fishers and the development of sustainable livelihood. Concerted action of pluralistic actors across the value chain is required for the operationalization of the extension-plus approach.